The role of the Church in civil society - Leonova Olga Georgiyevna (Studia Humanitatis, 2013)
The article reveals the materials of an international workshop on religious institutions in civil society, their support of humanitarian activities. The problems of mutual influence of religious institutions on political climate have been thoroughly discussed in the article.